2001
DOI: 10.1061/(asce)0899-1561(2001)13:4(306)
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Polymers for Use as Bitumen Modifiers

Abstract: The volume of waste polymer being produced continues to rise. Disposal is difficult and waste exceeds acceptable levels. The purpose ofthe research is to examine the possibility of incorporating waste polymer into bitumen as a modifier. The aim was to find recycled polymer modified binders that would be similar to proven modified binders or that would augment the properties of 100 penetration grade bitumen. A wide range of recycled polymers was tested including polyethylenes, polypropylenes, polyetherpolyureth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…It is not surprising that researchers have been very interested in incorporating waste polyethylene into asphalt pavements, as a modifier (Hinislioglu and Agar 2004;Edwards 2003;Panda and Mazumdar 2002;Murphy et al 2000Murphy et al , 2001Yousefi et al 2000;Morrison et al 1994;Liang 1993;Little 1993) or aggregate replacement (Zoorob 2000). However, using waste polyethylene as a modifier in hot-mix asphalt can be quite complicated.…”
Section: Introductionmentioning
confidence: 97%
“…It is not surprising that researchers have been very interested in incorporating waste polyethylene into asphalt pavements, as a modifier (Hinislioglu and Agar 2004;Edwards 2003;Panda and Mazumdar 2002;Murphy et al 2000Murphy et al , 2001Yousefi et al 2000;Morrison et al 1994;Liang 1993;Little 1993) or aggregate replacement (Zoorob 2000). However, using waste polyethylene as a modifier in hot-mix asphalt can be quite complicated.…”
Section: Introductionmentioning
confidence: 97%
“…(Berthelot et al, 2003;Krishnan and Rao, 2001). Murphy et al (2001) modifi ed asphalt binder using recycled polymers like polyethylenes, polypropylenes, polyetherpolyurethane and rubber. The performance was evaluated by measuring viscosity, penetration, softening point, aging and rheology.…”
Section: Influence Of Polymer Type and Structure On Polymer Modified mentioning
confidence: 99%
“…Khalid et al (1998) showed the correlation between the rheological properties of the binders in terms of the complex modulus (G * ) and the phase angle (d). Murphy et al (2001) studied recycled waste polymers for use as modified binders. Salab and Suparna (2000) reported that the recycled plastics modified mixes containing polypropylene (PP) and LDPE had better durability and fatigue life as compared with unmodified asphalt mix.…”
Section: Introductionmentioning
confidence: 99%